Perception Evaluation Kit: A Case Study with Materials and Learning Styles - Araya-Leon, M (Springer Science and Business Media B.V., 2022)
Materials are elements that configure our built environment and are key components in design and engineering education. This research aims to understand learners’ sensorial perception of materials as stimuli and what constitutes the most appropriate communication channel for learning about their characteristics without losing information in accordance with their VAK learning styles–visual, auditory and kinaesthetic–. Seventy-five people participated in this workshop. Using evaluation tools in a test format, they evaluated all the sensory properties of the following materials: Alusion™, PolarMoss, and Silkworms. These three materials were presented in various interaction formats, called channels: a text plus image–C1–, video–C2–, and a physical sample plus audio–C3–. Two types of experiments were carried out: mixed per person—interaction with the three materials in a different channel each time in random order—and blocked per person—interaction with the same material in the three channels, in an order of C1–C3. The data obtained was analysed using mixed models with the channel as a fixed factor and the individuals and material as the random factors. The most relevant results indicate significant differences between channels in accordance with the sensory property, normally C2 and C3. The level of responses between the two experiments is similar, therefore showing that the order C1–C2–C3 does not affect perception. Although the three learning styles–visual, auditory, and kinaesthetic–coexist in the participants, the vast majority agree that they prefer C3 as easier to evaluate, more entertaining and the best way to learn. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.